Current research issues related to post-wildfire runoff and erosion processes - Rick Shakesby (Earth-Science Reviews, 2013)
Post-wildfire effects were first reported in the USA in the 1930s and only later was research into the topic carried out elsewhere in the world. These effects are usually temporary, heterogeneous in time and space, sensitive to thresholds, and involve a variety of processes, which have typically been monitored using a variety of techniques. This variability in cause and effect have affected the success of post-fire research, but the large quantity of data from field monitoring that has now been collected from across the world would suggest that it ought now to be possible to assemble all the findings and improve our understanding of post-wildfire runoff and erosion responses. To achieve this goal, it is necessary to identify and place in order of priority the current issues facing post-wildfire runoff and erosion research. The most important issues are the need to: (1) identify both similarities and differences between post-wildfire responses around the world so that common patterns and generalities able to explain cause and effect relationships can be identified; (2) identify and quantify relationships between fire effects and the soil hydraulic properties that best able to represent the unusual conditions operating post-fire; (3) determine on burned terrain the effect of temporally and spatially variable rainstorms, often the main cause of enhanced post-wildfire runoff and erosion; (4) find functional relationships between precipitation, basin form, runoff connectivity, contributing area, surface roughness, depression storage, and sediment properties required in order to predict the timing, scale and duration of, for example, floods and debris flows from unmonitored burned basins; and (5) develop standard measurement methods so that comparable runoff and erosion data can be collected in the future. Resolving these issues can be expected to help in improving conceptual and computer models of post-wildfire runoff and erosion.